An Organocatalyzed Asymmetric Michael Addition of Cyclic Ketones to 1, 3‐Diene‐1, 1‐dicarboxylates. Issue 27 (5th August 2013) - Chowdhury, Raghunath; Ghosh, Sunil K.
Abstract: The purely organocatalyzed direct Michael addition of cycloalkanones to 1, 3‐diene‐1, 1‐dicarboxylates was effected by a combination of ( S )‐2‐(4‐toluenesulfonamidomethyl)pyrrolidine and acetic acid. Addition products were formed in high yield and with good regio‐, diastereo‐, and enantioselectivity. The catalysis took place through a dual activation mode, that is, a nucleophilic enamine activation of the donor ketone and an eletrophilic hydrogen‐bonding activation of the acceptor diene dicarboxylate. The addition products could easily undergo a stereoselective ketone reduction and subsequent lactonization to give compounds with high synthetic potential. Abstract : The addition of cyclic ketones to 4‐aryl‐1, 3‐diene‐1, 1‐dicarboxylates occurred exclusively in a 1, 4‐fashion in the presence of an organocatalyst under neat conditions at room temperature to give products in very good yield and with good diastereo‐ and enantioselectivity. These products could subsequently be functionalized to give compounds with high synthetic potential.